The Concurrent Validity of Using Simulated Patient and Real Patient in Communication Skills Assessment of Medical Students - Hosein Karimi-Moonagi; Roza Montazeri; Mahnaz Amini; Mohammad-Taghi Shakeri; Mehri Yavari; Mohammad Khajehdaluee; Mojgan Afkhamizadeh (Kerman University of Medical Sciences, 2014)
Background & Objective: Communication skills assessment requires the use of valid instruments The present study has done to investigate concurrent validity of the simulated patient meaning relationship between test results by the simulated or real patient and possibility to generalize the results by simulated patient and in simulated environment for real patient and in bedside   Methods: In this correlation study 32 medical externships were enrolled by purposive sampling method The students were divided randomly into two equal and homogeneous groups Using crossover design first group were assessed by real patient initially and then simulated patient and second group were measured conversely Communication skills assessment was done using a checklist retrieved from CalgaryCambridge interview skills checklist The data were analyzed using descriptive and analytical statistics   Results: In first assessment comparing scores by simulated and real patient in first group second group and total students showed significant differences In second assessment between two groups the statistics results was not significant with very minor differences (P = 0064) There were positive correlation between scores of total students by simulated and real patient (r = 063)   Conclusion: According to the results communication skills of each student in simulated position cannot be generalized to real situation and cannot be claimed that simulated patient can be used instead of real patient